Design of Compression Members for Durability - Josef Vican; Marian Sykora (Communications - Scientific letters of the University of Zilina, 2009)
General principles of structural elements design for durability and their application in the case of compression members are presented in this paper. The degradation effects of material deterioration due to corrosion cause the loss of member resistance, but the limit states method does not directly reflects design and verification allowing for failures caused by material deterioration. The time-dependent loss of compression member resistance was computed for specific corrosion models to express the time-dependent approximation function taking into account effects of corrosion degradation. Then, the design member resistance could be obtained using buckling member resistance multiplied by a timedependent function considering corrosion degradation effects within the member lifetime.